2019
DOI: 10.3847/1538-4357/ab4256
|View full text |Cite
|
Sign up to set email alerts
|

Variable Hard X-Ray Emission from the Central Star of the Eskimo Nebula

Abstract: The central star of NGC 2392 shows the hardest X-ray emission among central stars of planetary nebulae (CSPNe). The recent discovery of a spectroscopic companion with an orbital period of 1.9 days could provide an explanation for its hard X-ray emission, as well as for the collimation of its fast outflow. Here we analyse the available Chandra and XMM-Newton X-ray observations to determine accurately the spectral and temporal variation properties of the CSPN of NGC 2392. The X-ray emission can be described by a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The low luminosity 10 26 erg s −1 (and thus accretion rate) and plasma temperature ≈0.17-0.7 keV of the X-ray emission from G 29-38 is very different to those of systems with high accretion rates such as symbiotic stars and CVs (L X 10 31 erg s −1 and T X 1 keV; see Figure 3 in Guerrero et al 2019). The X-ray luminosity is also below that of putative single WDs with hard X-ray emission, which may still present plasmas at similar temperatures (L X ∼ 5 × 10 29 -5 × 10 31 erg s −1 and T X ∼ 0.1-1.5 keV; Chu et al 2021;S.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 90%
“…The low luminosity 10 26 erg s −1 (and thus accretion rate) and plasma temperature ≈0.17-0.7 keV of the X-ray emission from G 29-38 is very different to those of systems with high accretion rates such as symbiotic stars and CVs (L X 10 31 erg s −1 and T X 1 keV; see Figure 3 in Guerrero et al 2019). The X-ray luminosity is also below that of putative single WDs with hard X-ray emission, which may still present plasmas at similar temperatures (L X ∼ 5 × 10 29 -5 × 10 31 erg s −1 and T X ∼ 0.1-1.5 keV; Chu et al 2021;S.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 90%
“…Finally, it is worth noting that the central star of NGC 2392 has recently been recognized to be in a binary system (Miszalski et al 2019). Its orbital period is yet unsettled, as periodic radial velocity variations of 3 hours (Prinja & Urbaneja 2014) and 1.9 days (Miszalski et al 2019) and a hard X-ray emission modulation of 6 hours (Guerrero et al 2019) have been reported. The companion of the central star of NGC 2392 has been proposed to be a hot white dwarf as its effective temperature 43,000 K (Méndez et al 2012) cannot explain its high nebular excitation, being notably discrepant from the higher He ii Zanstra temperature (Heap 1977;Pottasch et al 2008;Miszalski et al 2019).…”
Section: Ngc 2392 In the Ecosystem Of Pnementioning
confidence: 99%
“…The hard X-ray emission from the CSPN of the Eskimo Nebula has been found to be variable with a period ≃6 hours [10]. This X-ray emission might be attributed to accretion of material from the CSPN wind onto a white dwarf companion, and thus the observed period can be assigned either to the orbital period of the companion or to the rotation of an accretion disk around it.…”
Section: X-ray Variability Studiesmentioning
confidence: 99%